Considerations and Caveats in Combating ESKAPE Pathogens against Nosocomial Infections. Issue 1 (5th December 2019) - Ma, Yu‐Xuan; Wang, Chen‐Yu; Li, Yuan‐Yuan; Li, Jing; Wan, Qian‐Qian; Chen, Ji‐Hua; Tay, Franklin R.; Niu, Li‐Na
Abstract: ESKAPE pathogens ( Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) are among the most common opportunistic pathogens in nosocomial infections. ESKAPE pathogens distinguish themselves from normal ones by developing a high level of antibiotic resistance that involves multiple mechanisms. Contemporary therapeutic strategies which are potential options in combating ESKAPE bacteria need further investigation. Herein, a broad overview of the antimicrobial research on ESKAPE pathogens over the past five years is provided with prospective clinical applications. Abstract : ESKAPE pathogens ( Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) are among the most common opportunistic pathogens in nosocomial infections. Herein, contemporary therapeutic strategies against drug‐resistance ESKAPE and antimicrobial agents with prospective clinical applications are summarized, with a forecast on the future tendency of ESKAPE infection control.